PENGARUH EFEKTIVITAS KEPEMIMPINAN TERHADAP KINERJA PELAYANAN SIPIL PADA DINAS KEPENDUDUKAN DAN CATATAN SIPIL KABUPATEN HALMAHERA UTARA - PAWATTE, ANDRIS; Kiyai, Burhanuddin; Tampi, Gustaf Budi (JURNAL ADMINISTRASI PUBLIK, 2015)
Abstract: This study aimed to: "analyze the impact of leadership effectiveness terhdap performance ofthe civil service in the Department of Population and Civil North Halmahera District". The relevantmethod used is descriptive and explanatory survey with quantitative approach. Semapel respondentspurposively set as many as 33 employees in the Department of Population and Civil Registration ofNorth Halmahera district. Data were collected through questionnaires by survey techniques and directobservation. Once the data is collected, then analyzed by using frequency tables analysis (percentage)and to test the hypothesis applied simple linear regression analysis and correlation of product moment.The result showed that (1) The effectiveness of leadership at the Department of Population andCivil Registration North Halmahera District, observed from the dimensions of leader-subordinaterelations, task structure and position power leader, is in the category were likely to be high.Dimensions of Leadership Effectiveness, partially highly significant and contributes greatly to theperformance of the civil service. (2) The performance of the civil service in the Department ofPopulation and Civil Registration Halmahera in middle category or medium tends to be high.Simultaneously (together) dimensions of leadership effectiveness and positive effect is very real andhad a contributive relation to the performance of the civil service, particularly in the Department ofPopulation and Civil Registration North Halmahera.Thus, we can conclude that the hypothesis proposed in this study can be tested empiricallyvalidity, as well as justifying the underlying theories. Referring to the findings in this study, it can besuggested that leaders at all levels in the Department of Population and Civil Registration NorthHalmahera further enhance the competence and ability of a leader to motivate employees to improvetheir performance in delivering to the public servant.Keywords: leadership effectiveness, the performance of the civil service.